Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2139/ssrn.2021326
|View full text |Cite
|
Sign up to set email alerts
|

The People’s Encyclopedia Under the Gaze of the Sages: A Systematic Review of Scholarly Research on Wikipedia

Abstract: Wikipedia has become one of the ten most visited sites on the Web, and the world's leading source of Web reference information. Its rapid success has inspired hundreds of scholars from various disciplines to study its content, communication and community dynamics from various perspectives. This article presents a systematic review of scholarly research on Wikipedia. We describe our detailed, rigorous methodology for identifying over 450 scholarly studies of Wikipedia. We present the WikiLit website (http://wik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 378 publications
1
57
0
5
Order By: Relevance
“…Thus, Wikipedia's production side has been the focus of numerous studies. A literature review by Okoli et al [15] covering 477 research studies on Wikipedia showed that 42% of the studies mostly centered on issues related to participation, i.e. how editors create and edit articles, resolve disputes, or organize their community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Wikipedia's production side has been the focus of numerous studies. A literature review by Okoli et al [15] covering 477 research studies on Wikipedia showed that 42% of the studies mostly centered on issues related to participation, i.e. how editors create and edit articles, resolve disputes, or organize their community.…”
Section: Introductionmentioning
confidence: 99%
“…Only 20% of the studies related to readers in Wikipedia, the usage side of Wikipedia, such as examining the popularity of articles or topics in Wikipedia. Less than 1% of the reviewed studies looked at users' reading preferences and only one study investigated reading behavior [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other formatting in titles cannot directly be handled in Wikidata's title property, 25 and recording a date such as "Summer 2011" is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This review of Wikipedia readership is part of a much larger review of scholarly research on all topics related to Wikipedia. In an overview paper of the entire project, we described our systematic review methodology in detail (Okoli et al., ), in which we identified more than 500 scholarly studies on Wikipedia published in English. In brief, we mainly focused on identifying peer‐reviewed journal publications and doctoral theses and tried to be as exhaustive as possible in identifying these.…”
Section: Introductionmentioning
confidence: 99%
“…Although all Wikipedia contributors are of course also readers, we restrict our focus here to topics that concern reading Wikipedia without substantial treatment of contribution. We cover issues related to Wikipedia contributors and participation in depth in a separate review (Okoli et al., ).…”
Section: Introductionmentioning
confidence: 99%